Uso de PHPSimplex y aprendizaje de optimización lineal en Tercer Año BGU de la Unidad Educativa José María Román 2021-2022. - Haro Mariño, José Luis (2023)
Linear optimization has been incorporated in the official curriculum of the ministry of education; however, it is not fully developed. Therefore, “The aim of this present research work is to develop a didactic teaching proposal for the management of PHPSimplex in the learning of linear optimization” for third-year BGU students at the José María Roman Educational Unit. This study will be able to improve the learning of linear optimization by structuring a didactic proposal that teachers can be used to develop student´s solving problem skills. The theoretical framework that supports the work was based on learning theories, didactic resources, and ICT. On the other hand, this is a fieldwork, so that, it was carried out in the context, and the quantitative research collection numerical data, a sample of 35 students. The design was non-experimental, variables which were not manipulated in the study. Finally, it has concluded that PHPSimplex is a useful and effective tool for learning linear optimization and allows students to visualize and solve problems in an interactive and efficient way, as a consequence the theorical concepts, help students more clearly and concretely for a better understanding.